A short-circuit-resistant, heat-resistant and energy-saving busbar
By using a combination of a copper-clad aluminum tube layer and a silane-modified silicone rubber insulating layer in the busbar, the problem of arc discharge and leakage marks in the short circuit fault of the busbar is solved, and efficient power saving and short-circuit resistance of the conductor are achieved.
Patent Information
- Application Number
- CN202411271666.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-11
AI Technical Summary
In short-circuit failures caused by factors such as insulation aging, filth and lightning strikes, existing busbars are prone to arc discharge and leakage mark damage, loss of electrical insulation performance, and threaten the safety and stability of the power system.
Using a copper-clad aluminum tube layer structure, combined with a silane-modified silicone rubber insulating layer and a copper foil shielding layer, the utilization rate of the conductor, compatibility and heat resistance of the insulating layer are improved, and the Shielding capability to charge.
It effectively reduces AC resistance, reduces losses, improves the short-circuit resistance of the conductor and the heat resistance of the insulating layer, ensures the low-temperature operation of the busbar under short-circuit conditions, reduces the risk of fire and explosion, and saves electricity.
Smart Images

Figure BDA0005038898120000081 
Figure BDA0005038898120000091 
Figure BDA0005038898120000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of busbars, in particular to a short-circuit-resistant, heat-resistant and energy-saving busbar. Background Art
[0002] The busbar is an important part of the power plant and substation. The busbar is connected to the generators, transformers, transmission lines, distribution lines and phase adjustment equipment of the power plant and substation. The reliability of the busbar will directly affect the reliability of the power plant and substation. In addition, the high-voltage busbar of the substation is also the central part of the power system. If the short-circuit fault of the busbar cannot be quickly removed, it will cause the accident to expand, destroy the stable operation of the power system, and cause the collapse of the power system. Therefore, the design of the busbar is one of the important links to ensure the safe operation of the power system. Although the busbar has fewer faults than the transmission lines exposed in the wild, the busbar also has the problem of short-circuit faults caused by insulation aging, dirt and lightning strikes, like other electrical equipment, and the consequences are very serious. There are many reasons for busbar failure, and one of them is that the current transformer or voltage transformer is damaged or exploded due to insulation aging, bushing leakage, etc., resulting in busbar short-circuit failure. Therefore, the selection of insulating materials is of great significance to busbar protection. Commonly used insulating materials are generally rubber, polyvinyl chloride, polyethylene, nitrile polyoxyethylene composites, etc. Among them, silicone rubber has excellent electrical insulation, high and low temperature resistance, hydrophobicity and hydrophobic migration and weather resistance. It has been widely used in various industries such as transportation, medical construction, power and electricity, and aerospace. However, silicone rubber has very poor compatibility with other polymers and fillers, and is prone to smoldering after encountering fire. In addition, external uncontrollable factors such as moisture, salt spray, dirt and strong electric fields may reduce the hydrophobicity of silicone rubber composites during use, causing leakage current on the surface of silicone rubber composites and arc discharge, which will eventually cause leakage tracking damage to silicone rubber composites and lose their electrical insulation properties, posing a huge threat to the safety and stability of the entire power system. Summary of the invention
[0003] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a short-circuit resistant heat-resistant energy-saving busbar, including a copper-clad aluminum tube layer, a shielding layer and an insulating layer, wherein the aluminum layer is a hollow aluminum tube with a thickness of 6 to 8 mm, the copper layer is tightly mechanically combined with the aluminum layer, the wall thickness of the copper layer is 2 to 3 mm, the thickness of the shielding layer is 4 to 5 mm, the thickness of the insulating layer is 5 to 7 mm, and the insulating layer includes 100 parts of silane-modified silicone rubber, 20 to 50 parts of fumed silica, and 2 to 5 parts of a low-molecular organic silicon compound by weight. , 10 to 30 parts of polyetheretherketone, 5 to 15 parts of mullite, and 2 to 8 parts of barium titanate. The silane-modified silicone rubber is an epoxidized silicone rubber grafted with a fluorosilane coupling agent and an aminosilane coupling agent; the silicone rubber is a methyl vinyl silicone rubber, and the vinyl content of the methyl vinyl silicone rubber is ≥1.8 mol%; the mass ratio of the aminosilane coupling agent to the fluorosilane coupling agent is (2 to 3):1, and the amount of the aminosilane coupling agent and the fluorosilane coupling agent added is 50 to 70 mol% of the vinyl content of the silicone rubber.
[0004] Copper, aluminum and their alloys are commonly used busbar conductor materials. Aluminum has good ductility and toughness, but its surface is easily oxidized. Copper has low resistivity, good conductivity, strong surface oxidation resistance, and is still conductive after oxidation, but it is relatively expensive. The present invention adopts copper for the outer layer and hollow aluminum tube for the inner core to form a copper-clad aluminum tube busbar. According to the skin effect principle, the thickness of the copper and aluminum tubes is reasonably matched to improve the utilization rate of copper, increase the surface area of the copper conductor, and improve the problem of the conductor current density non-uniformity coefficient. The wall thickness of the copper layer is 2-3 mm, which can distribute about 50% of the current; the aluminum layer is a hollow aluminum tube with a thickness of 6-8 mm, which can distribute 50% of the current. The current distribution is relatively uniform, the AC resistance is reduced, the loss is reduced, the rated current temperature rise can be reduced from 50K to 30K, the problem of easy aging of the insulating material due to excessive temperature is reduced, and the line loss is reduced. Compared with the traditional busbar, 23-64% of electric energy is saved, and the busbar temperature is still lower than 100° C. under the condition of a short circuit of 4 times the rated current for 5 minutes, the short circuit resistance of the conductor is improved, and fire and explosion can be effectively prevented.
[0005] The insulating layer uses silane-modified silicone rubber as epoxidized silicone rubber modified by fluorosilane coupling agent and aminosilane coupling agent, wherein the silicone rubber is first epoxidized and then mixed with fluorosilane coupling agent and aminosilane coupling agent. The epoxy group can increase the polarity of silicone rubber, thereby improving the compatibility of silicone rubber and polyetheretherketone material. In addition, some epoxy groups react with the amino groups in the aminosilane coupling agent to form a ring-opening reaction, thereby grafting the aminosilane coupling agent on the surface of the silicone rubber, thereby improving the compatibility of the silicone rubber with inorganic fillers such as fumed silica, mullite, and barium titanate; finally, the alkoxy groups at the other end of some aminosilane coupling agents are hydrolyzed under the action of water to produce silanol groups and condense with the silanol groups generated by the hydrolysis of the fluorosilane coupling agent, thereby grafting the hydrophobic fluorosilane coupling agent on the surface of the silicone rubber. Since the F atom has a large electronegativity and a low surface energy, the hydrophobicity, heat resistance and charge dissipation performance of the silicone rubber surface are improved. When a strong arc discharge occurs, the generated charge will be captured by the F atoms on the surface of the silicone rubber to form a charge shielding layer, reducing the accumulation of charge on the surface of the silicone rubber, thereby reducing the damage of the charge to the silicone rubber molecular chain, thereby effectively improving the short circuit resistance and heat resistance of the insulating layer.
[0006] Mullite and barium titanate are vitrifiable materials, and mullite contains a small amount of potassium oxide and sodium oxide. When short circuit leakage occurs, the potassium oxide and sodium oxide act as low melting point additives, bonding with mullite, barium titanate and other porcelain fillers to form a dense ceramic body, improving the flame retardant and leakage tracking resistance of silicone rubber. At room temperature, polyetheretherketone, mullite and barium titanate can improve the mechanical properties and heat resistance of silicone rubber. Barium titanate also has a high dielectric constant. When added in appropriate amounts, it can reduce the surface energy of silicone rubber, effectively reduce the adhesion of contaminants such as salt powder, coal powder or iron oxide, and further reduce the risk of short circuit.
[0007] Preferably, the shielding layer is any one of a copper foil shielding layer, a copper wire braided shielding layer, an aluminum foil shielding layer, and an aluminum wire braided shielding layer.
[0008] Preferably, the fluorosilane coupling agent is selected from one or more of 1H,1H,2H,2H-perfluoroheptadecantrimethyloxysilane, 1H,1H,2H,2H-perfluorodecyltrichlorosilane, perfluorohexylethyltrichlorosilane, perfluorohexylethyltrimethoxysilane, and perfluorohexylethyltriethoxysilane; the aminosilane coupling agent is selected from one or more of 3-aminopropyltriethoxysilane (KH-550), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (602), γ-aminopropylmethyldiethoxysilane (902), and γ-aminopropyltrimethoxysilane (KH-540).
[0009] Preferably, the polyetheretherketone is polyetheretherketone powder, and the melt viscosity measured at 400° C. according to standard ISO11443 is 100-200 Pa·s.
[0010] Preferably, the alumina content of the mullite is 50-65wt%.
[0011] Preferably, the barium titanate is nano-scale barium titanate with an average particle size of ≤100 nm.
[0012] Preferably, the low molecular weight organic silicon compound is at least one of diphenylsilanediol, methylphenyldiethoxysilane, tetramethylethylenedioxydimethylsilane, low molecular weight hydroxy silicone oil and silazane.
[0013] Preferably, the particle size of the fumed silica is 10 to 50 nm, and the specific surface area is 70 to 400 m 2 / g.
[0014] Preferably, the insulating layer further includes, by weight, 0.2 to 2 parts of antioxidant, 0.5 to 5 parts of lubricant, 10-30 parts of flame retardant, and 0.5 to 5 parts of colorant; the antioxidant is a primary antioxidant and an auxiliary antioxidant in a mass ratio of (1 to 2): 1; the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant; the lubricant is any one or more of low molecular weight esters, metal soaps, stearic acid complex esters, and amides; the flame retardant is one or more of magnesium hydroxide and aluminum hydroxide, and the colorant is one or more of an organic colorant and an inorganic colorant.
[0015] The method for preparing the insulating layer comprises the following steps:
[0016] S1. Preparation of epoxidized silicone rubber: Mix silicone rubber with chlorobenzene, stir and dissolve at 50-60°C to form a glue liquid, add m-chloroperoxybenzoic acid, continue stirring and reacting for 20-40 hours, lower the reaction temperature to below -20°C to precipitate the by-product m-chlorobenzoic acid, filter and collect the glue liquid, wash with sufficient methanol to precipitate the product epoxidized silicone rubber, and place the product in a vacuum oven at 50-60°C and dry for 12-24 hours to obtain epoxidized silicone rubber;
[0017] S2. Add the epoxidized silicone rubber, aminosilane coupling agent and triethylamine to a double-roll mill, mix at 50 to 60° C. for 20 to 40 minutes, add the fluorosilane coupling agent and mix, and spray a small amount of deionized water in the form of a spray, and continue mixing for 20 to 60 minutes to obtain an epoxidized silicone rubber modified with a fluorosilane coupling agent and an aminosilane coupling agent;
[0018] S3. Pass cooling water through the roller to reduce the mixing temperature to below 40°C, then add fumed silica, low molecular weight organic silicon compound, polyetheretherketone, mullite and barium titanate to the fluorosilane coupling agent and aminosilane coupling agent modified epoxidized silicone rubber in sequence, continue mixing for 20 to 40 minutes to produce sheets, use high-pressure steam continuous vulcanization to obtain the insulating layer material, and extrude the insulating layer material onto the outside of the shielding layer to obtain the insulating layer.
[0019] Beneficial Effects
[0020] The present invention provides a short-circuit-resistant, heat-resistant and energy-saving busbar, comprising a copper-clad aluminum tube layer, a shielding layer and an insulating layer, wherein the conductor layer improves the utilization rate of copper, increases the surface area of the copper conductor, and improves the problem of the uneven coefficient of the conductor current density by reasonably matching the thickness of the copper and aluminum tubes, so that the current distribution is relatively uniform, the AC resistance is reduced, and the loss is reduced, and the rated current temperature rise can be reduced from 50K to 30K, reducing the problem of easy aging of the insulating material due to excessive temperature, and reducing line loss. The insulating layer uses silane-modified silicone rubber as a fluorosilane coupling agent and an aminosilane coupling agent to modify the epoxy silicone rubber, which improves the compatibility of silicone rubber with polyetheretherketone materials and inorganic fillers such as fumed silica, mullite, and barium titanate, and increases the room temperature mechanical properties and heat resistance of silicone rubber. In addition, the addition of the fluorosilane coupling agent also improves the hydrophobicity and charge dissipation performance of the silicone rubber surface, so that the surface of the insulating layer reduces the attachment of contaminants such as salt powder, coal powder or iron oxide, thereby improving the short-circuit resistance of the insulating layer. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0023] The raw materials used in the embodiments and comparative examples are described below:
[0024] Silicone rubber 1: methyl vinyl silicone rubber, model 112-7, vinyl content of 1.8-5 mol%, measured value of 3%, purchased from Dongjue Silicone;
[0025] Silicone rubber 2: methyl vinyl silicone rubber, model 112-6, vinyl content of 0.8-1.79 mol%, measured value of 1.2%, purchased from Dongjue Silicone;
[0026] Fluorosilane coupling agent: 1H,1H,2H,2H-perfluoroheptadecantrimethyloxysilane, purchased from Shanghai MacLean;
[0027] Aminosilane coupling agent: 3-aminopropyltriethoxysilane, KH-550, purchased from Shanghai Macklin;
[0028] Triethylamine: purchased from Shanghai MacLean;
[0029] Fumed silica: average particle size is 50nm, specific surface area is 200m 2 / g, model AM-SiO2-021-2, purchased from Zhejiang Yamei Technology;
[0030] Low molecular weight organosilicon compound: methylphenyldiethoxysilane, purchased from Aladdin;
[0031] Polyetheretherketone 1: polyetheretherketone powder, melt viscosity of 130 Pa·s measured at 400°C according to standard ISO11443, model VICTREX PEEK 150P, purchased from Victrex;
[0032] Polyetheretherketone 2: polyetheretherketone powder, melt viscosity of 90 Pa·s measured at 400°C according to standard ISO11443, model VICTREX PEEK 90P, purchased from Victrex;
[0033] Polyetheretherketone 3: polyetheretherketone powder, melt viscosity of 300 Pa·s measured at 400°C according to standard ISO11443, model VICTREX PEEK 380P, purchased from Victrex;
[0034] Mullite 1: alumina content 59.95wt%, model HM-60, purchased from Huaihua Huaheng Mullite Co., Ltd.;
[0035] Mullite 2: alumina content 43.1wt%, model HM-45, purchased from Huaihua Huaheng Mullite Co., Ltd.;
[0036] Mullite 3: alumina content 71.3wt%, model HM-70, purchased from Huaihua Huaheng Mullite Co., Ltd.;
[0037] Barium titanate 1: average particle size ≤ 100 nm, model TX83650-500g, purchased from Yingxin Laboratory;
[0038] Barium titanate 2: average particle size <3 μm, model TX83650-500g-A, purchased from Yingxin Laboratory;
[0039] Antioxidant: a mixture of antioxidant 1010 (SONOX) and antioxidant 168 (SONOX) in a mass ratio of 1:2, commercially available;
[0040] Lubricant: zinc stearate, commercially available;
[0041] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0042] Preparation of epoxidized silicone rubber 1
[0043] Take silicone rubber 1 and chlorobenzene and mix them. Stir and dissolve them at 55°C to form a glue liquid with a concentration of 4g / 100ml. Add m-chloroperbenzoic acid at a molar ratio of vinyl group to peroxide group of 1:1.3. Continue stirring and reacting for 40 hours. Lower the reaction temperature to below -20°C to precipitate by-product m-chlorobenzoic acid. Filter and collect the glue liquid. Wash it three times with sufficient methanol to precipitate the product epoxidized methyl vinyl silicone rubber. Dry the product in a vacuum oven at 55°C for 24 hours to obtain epoxidized silicone rubber 1.
[0044] Preparation of epoxidized silicone rubber 2
[0045] The preparation method is the same as that of the epoxidized silicone rubber 1, except that the silicone rubber 1 is replaced by the silicone rubber 2.
[0046] Preparation of silane-modified silicone rubber 1
[0047] Epoxidized silicone rubber, aminosilane coupling agent and triethylamine were added to a double-roll mill, mixed at 55° C. for 40 minutes, then a fluorosilane coupling agent was added and mixed, and a small amount of deionized water was sprayed in the form of a spray, and the mixing was continued for 60 minutes to obtain fluorosilane coupling agent and aminosilane coupling agent modified epoxidized silicone rubber; wherein the mass ratio of aminosilane coupling agent to fluorosilane coupling agent was 2:1, the amount of aminosilane coupling agent and fluorosilane coupling agent added was 50 mol% of the vinyl content of the silicone rubber, and the amount of triethylamine added was 0.05 wt% of the total mass of aminosilane coupling agent and fluorosilane coupling agent, to obtain silane modified silicone rubber 1.
[0048] Preparation of silane-modified silicone rubber 2
[0049] The preparation method is the same as that of the silane-modified silicone rubber 1, except that the mass ratio of the aminosilane coupling agent to the fluorosilane coupling agent is 1:2.
[0050] Preparation of silane-modified silicone rubber 3
[0051] The preparation method is the same as that of silane-modified silicone rubber 1, except that the amount of aminosilane coupling agent and fluorosilane coupling agent added is 120 mol% of the vinyl content of the silicone rubber.
[0052] Preparation of silane-modified silicone rubber 4
[0053] The preparation method is the same as that of the silane-modified silicone rubber 1, except that the epoxidized silicone rubber 1 is replaced by the epoxidized silicone rubber 2.
[0054] Preparation of silane-modified silicone rubber 5
[0055] Epoxidized silicone rubber 1 and aminosilane coupling agent were added to a double-roll mill, mixed at 40°C for 40 minutes, then fluorosilane coupling agent was added and mixed, and a small amount of deionized water was sprayed in the form of a spray, and mixing was continued for 60 minutes to obtain fluorosilane coupling agent and aminosilane coupling agent modified epoxidized silicone rubber; wherein the mass ratio of aminosilane coupling agent to fluorosilane coupling agent was 2:1, and the amount of aminosilane coupling agent and fluorosilane coupling agent added was 50 mol% of the vinyl content of the silicone rubber, to obtain silane-modified silicone rubber 5.
[0056] Preparation of silane-modified silicone rubber 6
[0057] The preparation method is the same as that of silane-modified silicone rubber 1, except that no fluorosilane coupling agent is added.
[0058] Preparation of silane-modified silicone rubber 7
[0059] The preparation method is the same as that of silane-modified silicone rubber 1, except that no aminosilane coupling agent is added.
[0060] Preparation of insulation material
[0061] Cooling water is passed through the roller to reduce the mixing temperature to below 40°C, and fumed silica, low molecular weight organic silicon compound, polyetheretherketone, mullite, barium titanate, antioxidant (if any), and lubricant (if any) are added to the mixed silane-modified silicone rubber in sequence, and the mixing is continued for 20 to 40 minutes, and the sheet is produced, and the insulating layer material is obtained by continuous vulcanization with high-pressure steam. The specific composition and proportion of the insulating layer material are shown in Table 1.
[0062] Table 1 Specific composition and ratio of insulating layer materials (parts by weight)
[0063]
[0064]
[0065] Table 1 Specific composition and proportion of insulating layer materials (parts by weight)
[0066]
[0067]
[0068] Examples 1 to 8
[0069] A short-circuit-resistant, heat-resistant and energy-saving busbar comprises a copper-clad aluminum tube layer, a shielding layer and an insulating layer, wherein the aluminum layer is a hollow aluminum tube with a thickness of 7 mm, the copper layer is tightly mechanically bonded to the aluminum layer, the wall thickness of the copper layer is 2 mm, the shielding layer is 4 mm thick, the insulating layer is 6 mm thick, and the shielding layer is a copper foil shielding layer; the insulating layer is obtained by extruding insulating layer materials 1 to 8 obtained by mixing and vulcanizing the above insulating layer formula outside the cable shielding layer.
[0070] Comparative Examples 1 to 11
[0071] Compared with Examples 1 to 8, the difference is that the insulating layer is obtained by extruding insulating layer materials 9 to 19 obtained by mixing and vulcanizing the above insulating layer formula outside the cable shielding layer.
[0072] Comparative Example 12
[0073] A short-circuit-resistant, heat-resistant and energy-saving busbar comprises a copper-clad aluminum tube layer, a shielding layer and an insulating layer, wherein the aluminum layer is a hollow aluminum tube with a thickness of 10 mm, the copper layer is tightly mechanically bonded to the aluminum layer, the wall thickness of the copper layer is 1.5 mm, the shielding layer is 4 mm thick, the insulating layer is 6 mm thick, and the shielding layer is a copper foil shielding layer; the insulating layer is obtained by extruding an insulating layer material 3 obtained by mixing and vulcanizing the above-mentioned insulating layer formula outside a cable shielding layer.
[0074] The short-circuit-resistant, heat-resistant and energy-saving busbar and insulation layer materials prepared in Examples 1-8 and Comparative Examples 1-12 were subjected to the following performance tests, and the results are shown in Table 2.
[0075] 1. Rated temperature rise: Rated current 4000A, refer to the method in "Temperature rise analysis and experiment of new energy-saving copper-clad aluminum tube busbar" to test the temperature rise of the busbar;
[0076] 2. Short-circuit temperature rise: Rated current is 4000A, 4 times rated current short circuit, lasting 5 minutes, refer to the method in "Temperature Rise Analysis and Experiment of New Energy-Saving Copper Clad Aluminum Tube Busbar" to test the temperature rise of the busbar;
[0077] 3. Withstand voltage test: Select a starting voltage that is a multiple of 250V. From the start, increase the voltage by 250V every hour until breakdown occurs as described in Standard A of GB / T 6553-2003. Record the highest voltage tolerated before breakdown occurs.
[0078] 4. Tensile strength: According to the national standard "GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for thin plastics and sheets", the insulating layer material is cut into a dumbbell shape as required and tested using a SANS electronic tensile testing machine.
[0079] 5.CTI test: The test is carried out in accordance with the national standard "GB / T 6553-2003 Test method for evaluating the resistance of electrical insulating materials to tracking and corrosion under harsh environmental conditions". A voltage of 4.5kV is applied to both ends of the insulating material while dripping dirty liquid. The time required for the sample to burn through is tested. The longer the burn-through time, the better the heat resistance.
[0080] Table 2 Performance test results of embodiments and comparative examples
[0081]
[0082]
[0083] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A short-circuit-resistant, heat-resistant and energy-saving busbar, characterized in that: The invention comprises a copper-clad aluminum tube layer, a shielding layer and an insulating layer, wherein the aluminum layer is a hollow aluminum tube with a thickness of 6 to 8 mm, the copper layer is tightly mechanically bonded to the aluminum layer, the wall thickness of the copper layer is 2 to 3 mm, the thickness of the shielding layer is 4 to 5 mm, the thickness of the insulating layer is 5 to 7 mm, and the insulating layer comprises, by weight, 100 parts of silane-modified silicone rubber, 20 to 50 parts of fumed silica, 2 to 5 parts of low molecular weight organic silicon compounds, 10 to 30 parts of polyetheretherketone, and 5 to 6 parts of mullite. 15 parts, 2-8 parts of barium titanate, the silane-modified silicone rubber is fluorosilane coupling agent and aminosilane coupling agent graft-modified epoxidized silicone rubber; the silicone rubber is methyl vinyl silicone rubber, and the vinyl content of the methyl vinyl silicone rubber is ≥1.8 mol%; the mass ratio of the aminosilane coupling agent to the fluorosilane coupling agent is (2-3):1, and the added amount of the aminosilane coupling agent and the fluorosilane coupling agent is 50-70 mol% of the vinyl content of the silicone rubber.
2. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The shielding layer is any one of a copper foil shielding layer, a copper wire braided shielding layer, an aluminum foil shielding layer, and an aluminum wire braided shielding layer.
3. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The fluorosilane coupling agent is selected from one or more of 1H, 1H, 2H, 2H-perfluoroheptadecantrimethyloxysilane, 1H, 1H, 2H, 2H-perfluorodecyltrichlorosilane, perfluorohexylethyltrichlorosilane, perfluorohexylethyltrimethoxysilane, and perfluorohexylethyltriethoxysilane; the aminosilane coupling agent is selected from one or more of 3-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, and γ-aminopropyltrimethoxysilane.
4. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The polyetheretherketone is polyetheretherketone powder, and the melt viscosity measured at 400° C. according to standard ISO11443 is 100-200 Pa·s.
5. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The alumina content of the mullite is 50-65wt%.
6. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The barium titanate is nano-scale barium titanate with an average particle size of ≤100nm.
7. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The low molecular weight organic silicon compound is at least one of diphenylsilanediol, methylphenyldiethoxysilane, tetramethylethylenedioxydimethylsilane, low molecular weight hydroxy silicone oil and silazane.
8. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The average particle size of the fumed silica is 10 to 50 nm, and the specific surface area is 70 to 400 m 2 / g.
9. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The insulating layer further comprises, by weight, 0.2 to 2 parts of an antioxidant, 0.5 to 5 parts of a lubricant, 10 to 30 parts of a flame retardant, and 0.5 to 5 parts of a colorant; the antioxidant is a primary antioxidant and an auxiliary antioxidant in a mass ratio of (1 to 2):1; the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant; the lubricant is any one or more of low molecular weight esters, metal soaps, stearic acid complex esters, and amides; the flame retardant is one or more of magnesium hydroxide and aluminum hydroxide, and the colorant is one or more of an organic colorant and an inorganic colorant.
10. The short-circuit resistant, heat-resistant and energy-saving busbar according to claim 1, characterized in that: The method for preparing the insulating layer comprises the following steps: S1. Preparation of epoxidized silicone rubber: Mix silicone rubber with chlorobenzene, stir and dissolve at 50-60°C to form a glue liquid, add m-chloroperoxybenzoic acid, continue stirring and reacting for 20-40 hours, lower the reaction temperature to below -20°C to precipitate the by-product m-chlorobenzoic acid, filter and collect the glue liquid, wash with sufficient methanol to precipitate the product epoxidized silicone rubber, and place the product in a vacuum oven at 50-60°C and dry for 12-24 hours to obtain epoxidized silicone rubber; S2. Add the epoxidized silicone rubber, aminosilane coupling agent and triethylamine to a double-roll mill, mix at 50 to 60° C. for 20 to 40 minutes, add the fluorosilane coupling agent and mix, and spray a small amount of deionized water in the form of a spray, and continue mixing for 20 to 60 minutes to obtain an epoxidized silicone rubber modified with a fluorosilane coupling agent and an aminosilane coupling agent; S3. Pass cooling water through the roller to reduce the mixing temperature to below 40°C, then add fumed silica, low molecular weight organic silicon compound, polyetheretherketone, mullite and barium titanate to the fluorosilane coupling agent and aminosilane coupling agent modified epoxidized silicone rubber in sequence, continue mixing for 20 to 40 minutes to produce sheets, use high-pressure steam continuous vulcanization to obtain the insulating layer material, and extrude the insulating layer material onto the outside of the shielding layer to obtain the insulating layer.
Citation Information
Patent Citations
Direct-current-tracking-resistant electric insulation silicone rubber and preparation method thereof
CN111334047A
High-conductivity cable special for high-voltage power transmission
CN113903520A